Silvia Molina, La familia vino del norte. Et l’Histoire, d’où nous vient-elle ? - Marie-Agnès Palaisi-Robert (Caravelle)
Since 1916 and Los de abajo, there has been a great number of novels, especially those written by women which have rewritten the Mexican Revolution’s history. La familia vino del norte by Silvia Molina belongs to this literary genealogy and proposes a very valuable reflection about History, its writing and historiography.